Cities and global governance new sites for international relations - Amen, Michael Mark (Global interdisciplinary studies series, 2011)
Improves our understanding of the significance of 'the city' in global governance. This title calls for innovation in international relations theory with case studies that add breadth to theorizing the role sub-national political actors play in global affairs.